Evidence for interplay between genes and parenting on infant temperament in the first year of life: monoamine oxidase A polymorphism moderates effects of maternal sensitivity on infant anger proneness. (6th June 2013) - Pickles, Andrew; Hill, Jonathan; Breen, Gerome; Quinn, John; Abbott, Kate; Jones, Helen; Sharp, Helen
<x xml:space="preserve">Abstract</x> Background The low expression polymorphism of the MAOA gene in interaction with adverse environments (G × E) is associated with antisocial behaviour disorders. These have their origins in early life, but it is not known whether MAOA G × E occurs in infants. We therefore examined whether MAOA G × E predicts infant anger proneness, a temperamental dimension associated with later antisocial behaviour disorders. In contrast to previous studies, we examined MAOA G × E prospectively using an observational measure of a key aspect of the infant environment, maternal sensitivity, at a specified developmental time point. Methods In a stratified epidemiological cohort recruited during pregnancy, we ascertained MAOA status (low vs. high expression alleles) from the saliva of 193 infants, and examined specific predictions to maternal report of infant temperament at 14 months from maternal sensitivity assessed at 29 weeks of age. Results Analyses, weighted to provide general population estimates, indicated a robust interaction between MAOA status and maternal sensitivity in the prediction of infant anger proneness (p = .003) which became stronger once possible confounders for maternal sensitivity were included in the model (p = .0001). The interaction terms were similar in males (p = .010) and females (p = .016), but the effects were different as a consequence of an additional sex of infant by maternal sensitivity interaction. Conclusions This prospective study provides the first evidence of moderation by the MAOA gene of effects of parenting on infant anger proneness, an important early risk for the development of disruptive and aggressive behaviour disorders.